Makna Tradisi Ruwatan Cukur Rambut Gembel Sebagai Praktik Budaya Keagamaan Masyarakat Nahdliyin - Wahyu Khoirurrohman Sugiarto (Journal of Nahdlatul Ulama Studies, 2024)
The tradition of ruwatan (ritual cleansing) through the shaving of gembel (dreadlocked) hair in the Dieng Plateau is an inherited religio-cultural practice, understood as an effort to liberate children from sukerta/sesuker (misfortune) while simultaneously serving as an act of spiritual striving to draw closer to God. This tradition endures because it is sustained by a cultural value system and a symbolic language, and is further reinforced by folklore concerning Kyai Kolodete and Nini Roro Ronce as forms of symbolic authority that normalize ruwatan as a mechanism for restoring social and cosmological order. This study formulates three questions: (1) how the ruwatan of shaving gembel hair is understood by the Dieng community as a Nahdliyin religio-cultural practice; (2) how ruwatan functions as a rite of safety and a social mechanism in managing the symbolism of gembel hair and children’s behavior; and (3) how the tradition transforms from a family-based rite into mass ruwatan and tourism packaging within the Dieng Culture Festival. Employing a qualitative fieldwork-based approach, data were collected through observation, interviews, documentation, and field notes; analysis proceeded through data organization, coding, categorization, thematic synthesis, and the development of naturalistic generalizations (Anggito & Setiawan, 2018; Creswell, 2014). The findings affirm that ruwatan is a rite of release from sukerta that operates in two ways: restoring family peace of mind and reaffirming social order through religious processes (prayers/recitations, communal feasts) and traditional symbols. Gembel hair is understood not merely as a biological fact, but as an identity marker attached to origin narratives, making ruwatan a “gateway of legitimacy” that transforms the child’s status from vulnerable to safe. This article recommends strengthening meaning literacy (education on symbols and values) so that the tradition is not reduced to mere formality or spectacle. In addition, festival governance should balance cultural preservation and the tourism economy with safeguarding ritual sacredness through the involvement of religious figures and local communities, particularly to reinforce religious orientation and cultural ethics among younger generations.